Novel nanobody-161 binds tumor necrosis factor receptor 2 (TNFR2) to exert an anti-tumor effect but does not block TNFα-binding - Huang, Liang; Kong, Chao; Hu, Yuhao; Zhang, Michael; Li, Shuangqi; Wang, Wanjing; Guan, Hui; Lim, Mei Ling; Zhang, Zhen; Zhang, Wenhai; Zheng, Hailiang; Yan, Xintian; et al. (Frontiers in Immunology, 2025)
BackgroundTumor necrosis factor receptor 2 (TNFR2) is expressed on regulatory T cells (Tregs) and many cancer cells indicating its potential as a therapeutic target. Traditional non-blocking antagonists often disrupt immune homeostasis by excessively suppressing Treg cell function when blocking the TNFα signaling pathway, weakening the body’s antitumor immune response. A novel anti-cancer mechanism for targeting TNFR2 is presented and clinical potential discussed.MethodsA novel humanized anti-TNFR2 nanobody, Nanobody-161, was identified from the Sanyou Bio Super Trillion Antibody Library in the current work and the non-blocking effect of Nanobody-161 in TNFα-TNFR2 signaling investigated. A transgenic mouse model was established to investigate its anti-tumor activity. The crystal structure of the complex with TNFR2 was also analyzed.ResultsNanobody-161 had antitumor activity in a transgenic mouse model, reducing tumor weight by 5-fold at a dose of 7.5 mg/kg and inhibited TNFα-TNFR2 signaling in HEK293 cells overexpressing human TNFR2 with 10-fold greater potency than traditional antagonists. Nanobody-161 was not observed to disrupt TNFα-induced Treg proliferation in peripheral blood mononuclear cells. Nanobody-161 mediated Fc-dependent CD8+ T cell activation and TNFR2+ Tregs in the tumor microenvironment were depleted by antibody-dependent cell-mediated cytotoxicity (ADCC). The structure of Nanobody-161 VHH in complex with TNFR2 was determined at 2.9 Å resolution and epitopes of TNFR2 CRD2 and CRD3 were identified. Nanobody-161 may inhibit TNFR2 oligomerization but was not observed to block TNFα binding.ConclusionNanobody-161 is a novel non-blocking TNFR2-antogonist that inhibits tumor growth without causing immunosuppression and is a promising candidate for safer and more effective therapy of solid tumors.